1984
DOI: 10.1172/jci111450
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of immunoglobulins and plasma proteins from the jejunal mucosa. Transport rate and origin of polymeric immunoglobulin A.

Abstract: This closely corresponds to the 35 and 24% of IgA2 plasmocytes in jejunal mucosa and peripheral lymph nodes, respectively. (b) For each protein, a relative coefficient of excretion (RCE) was calculated (jejunum to serum concentration ratio expressed relative to that of albumin). RCEs of 1.41 for orosomucoid, 1.0 for albumin, 0.83 for IgG, and 0.74 for IgE and, in the deficient patient, of 0.64 for m-IgA and 0.016 for IgM were obtained. This was inversely related to the molecular weight of these proteins and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 38 publications
6
55
0
1
Order By: Relevance
“…The dose was estimated to correspond to the daily amount of IgA synthesised and secreted throughout the bowel in man. 10 The placebo group received an equivalent volume of Haemaccel (Behringwerke AG, Marburg, Germany) three times daily during the same period. This substance was used because it was regarded as inert and had a colour, taste and consistency very similar to the immunoglobulin preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The dose was estimated to correspond to the daily amount of IgA synthesised and secreted throughout the bowel in man. 10 The placebo group received an equivalent volume of Haemaccel (Behringwerke AG, Marburg, Germany) three times daily during the same period. This substance was used because it was regarded as inert and had a colour, taste and consistency very similar to the immunoglobulin preparation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of this quantity in the assessment of inflammatory bowel disease activity remains controversial (3,4). Owing to the absence of a specific mucosal transfer system, the monomeric IgA of intestinal secretions appears to be derived mainly from passive transport of plasma monomeric IgA (5,6). These monomeric IgA are relatively resistant to intestinal proteases and are found in the faeces in their native form or as fragments often bound to a r antiproteinase or pigments (7 -9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their intestinal clearance appears to be markedly increased during diarrhoea (10). Jonard et al have demonstrated that IgG, present in the intestinal secretions of healthy subjects, are serum-derived (5). We therefore evaluated the value of determining monomeric IgA and IgG intestinal clearances, together with that of aiantiproteinase, for the purpose of exploring the degree of intestinal protein loss syndrome, which in turn is related to mucosal permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is also the target of specific receptors and proteases produced by a number of pathogenic bacteria (6). Blood also contains a large quantity [average, 2 mg/ml (7)] of predominantly monomeric IgA; this circulating pool is largely independent ofthe mucosal pool in humans (8).…”
mentioning
confidence: 99%